Arg2P: an argumentation framework for explainable intelligent systems. (25th January 2022) - Calegari, Roberta; Omicini, Andrea; Pisano, Giuseppe; Sartor, Giovanni
Abstract: In this paper we present the computational model of Arg2 P, a logic-based argumentation framework for defeasible reasoning and agent conversation particularly suitable for explaining agent intelligent behaviours. The model is reified as the Arg2 P technology, which is presented and discussed both from an architectural and a technological perspective so as to point out its potential in the engineering of intelligent systems. Finally, an illustrative application scenario is discussed in the domain of computable law for autonomous vehicles.